Total and subregional thalamic volumes before and after cognitive behavioral therapy in obsessive-compulsive disorder - Vilde Brecke; Anders Lillevik Thorsen; Chaim Huyser; Niels de Joode; Bjarne Hansen; Kristen Hagen; Gerd Kvale; Chris Vriend; Odile A. van den Heuvel; Olga Therese Ousdal (Journal of Affective Disorders Reports)
Background: Thalamic volumetric alterations are frequently reported in children and adults with obsessive-compulsive disorder (OCD). However, whether successful cognitive behavioral therapy (CBT) is accompanied by thalamic macrostructural plasticity is unclear. Methods: Twenty-five pediatric (8–19 years) and 53 adult (16–55 years) OCD patients underwent magnetic resonance imaging before and after CBT with exposure and response prevention (CBT with ERP). The data also included 27 pediatric and 37 adult healthy controls that were scanned at similar time intervals. Thalamic nuclei volumes were estimated from T1-weighted images using the longitudinal stream of FreeSurfer's ThalamicNuclei pipeline and aggregated into five subregions (anterior, lateral, medial, pulvinar and ventral). Repeated measures ANCOVAs and linear models were used to investigate pre-post changes in total or subregional thalamic volumes and their associations with clinical response. Results: There were no significant changes in total or subregional thalamic volumes following CBT with ERP in the pediatric or the adult OCD patients. Moreover, the individual clinical response was not associated with changes in thalamic volume, and baseline thalamic volumes did not predict clinical outcome. Limitations: Low variance in the clinical outcome and power to detect only moderate-to-large effect sizes. Conclusion: The results suggest that total and subregional thalamic volumes remain stable following successful CBT with ERP in OCD patients. Hence, thalamus or its subregions may not serve as feasible biomarkers of CBT outcome in OCD.